Ageing and vision impairment : activity, independence and life satisfaction : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Rehabilitation at Massey University, Palmerston North, Aotearoa/New Zealand - Good, Gretchen Ann (Massey University, 2005)
Vision impairment profoundly affects older people, yet we do not know specifically which areas of daily living are most affected by vision impairment. Nor do we know how daily levels of activity and independence differ for this population compared to others their age. Understanding these differences can enhance goal-setting practices and improve rehabilitation services for older individuals with impaired vision. This study examined activity, independence and life satisfaction of older adults living in the Manawatu region of the North Island of New Zealand, using an adapted model of the World Health Organization's International Classification of Functioning, Disability and Health. The adapted model introduced subjective dimensions of functioning including satisfaction with activity, independence and life. This study was conducted with registered members of the Royal New Zealand Foundation of the Blind and with a random selection of registered voters in the region. Results indicated that both age and vision impairment had significant main effects on activity and independence. An interaction of age and vision had effect on the number of recently relinquished activities participants reported, social comparisons of activity and independence, and on satisfaction with independence and with life. An examination of age cohorts assisted in an improved understanding of daily functioning for this population. Unique findings were that social comparison of activity and satisfaction with social support contributed more to overall life satisfaction than did activity and independence levels. Unexpectedly, the oldest age cohort of those with impaired vision reported a higher level of overall life satisfaction than did their sighted peers in the oldest age cohort or younger cohorts with impaired vision. Results of this study will enable a better understanding of daily life for older people, and the differences which can be attributed to vision impairment. Older people and those that provide rehabilitation services to them can use this information to set more realistic and appropriate goals for rehabilitation. The results of this study will also allow those involved in personnel preparation programmes to develop curricula to improve new practitioners' understanding of typical daily life of older people with and without impaired vision.
Keywords: Impaired vision in older people; Blindness; Fields of Research::320000 Medical and Health Sciences::321200 Public Health and Health Services::321212 Care for disabled